Inhibition of prolactin promotes secondary skin follicle activation in cashmere goats. (10th March 2021) - Zhang, Lechao; Duan, Chunhui; Guo, Yunxia; Zhang, Yingjie; Liu, Yueqin
Abstract: The aim of this study was to investigate the involvement of prolactin (PRL) on development of secondary skin follicles in cashmere goats. Goats were randomly assigned to either a bromocriptine treatment or control group. Samples of cashmere fiber, blood, and skin were collected from all goats after 1 mo. The results indicated that the length, growth rate, and diameter of fibers were not influenced ( P > 0.05) by the inhibition of PRL resulting from the treatment with bromocriptine. There was a tendency for increases in total follicle number, primary and secondary follicle numbers, and in the ratio of secondary to primary follicles following treatment with bromocriptine, but these differences were not significant ( P > 0.05). The percentage of active secondary follicles in anagen was increased ( P < 0.05) in the bromocriptine-treated goats, but there was no effect of treatment on the percentage of active primary follicles. Bromocriptine decreased ( P < 0.05) circulating concentrations of PRL and Insulin-like growth factor 1 (IGF1) and increased ( P < 0.05) those of melatonin (MT), but there was no effect of this treatment on the serum concentrations of cortisol, growth hormone, tetraiodothyronine, and triiodothyronine. In bromocriptine-treated goats, mRNA expressions of PRL and MT membrane receptor 1a (MTNR1a) were decreased ( P < 0.05) and mRNA expression of MT nuclear receptor (RORα) was increased ( P < 0.05), but there was no effect of the treatment on expression of long PRL receptor, short PRL receptor, MT membrane receptor 1b and IGF1. It is concluded that inhibition of PRL promotes secondary hair follicle development in the anagen phase, possibly by downregulating MTNR1a and up-regulating RORα gene expression in the skin.